5 - Rethinking the Functionality of the Multinational Joint Task Force in Managing the Boko Haram Crisis in the Lake Chad Basin - Albert, Isaac Olawale (Africa Development, 2017)
The countries in the Lake Chad Basin (LCB) established the Multinational Joint Task Force (MNJTF) in April 2012 and upgraded it in 2015 for managing the ongoing Boko Haram crisis that started in Nigeria in 2002. The decision followed the realization that the problem is not necessarily Nigerian, as initially perceived, but a regional question. This security management formation is with a counter-terrorism mandate. This article takes a critical look at the challenges in the functioning of the security regimen. The most critical of the problems is that, though the countries need to work collaboratively at dealing with a common enemy, they are suspicious of each other over border issues. Nigeria is suspicious of Cameroon and Chad, which are in turn suspicious of Nigeria. This factor has reduced the effectiveness of this security community. The lesson here is that African states need to work on their relations timeously to enable them have smooth working relationship when they have to face a common enemy.